2004
DOI: 10.1210/en.2003-1078
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Oocyte Microvilli Development in the Baboon Fetal Ovary by Estrogen

Abstract: We recently showed that the number of primordial follicles was reduced by 50% in ovaries of near-term fetal baboons deprived of estrogen in utero and restored to normal in animals supplemented with estrogen. Oocytes are avascular and rely on surrounding granulosa cells for nutrients, a process facilitated by microvilli on the oocyte surface. However, our understanding of oocyte microvillus development in the primate fetal ovary is incomplete. Thus, we determined whether estrogen regulates formation of oocyte m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 26 publications
6
30
2
Order By: Relevance
“…These results correspond with the recent data indicating the ERs expression in the mouse (Wu et al 1992), baboon (Zachos et al 2004) and human oocytes (Wu et al 1993). This suggests that a paracrine effect of estrogens is exerted on oocyte maturation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results correspond with the recent data indicating the ERs expression in the mouse (Wu et al 1992), baboon (Zachos et al 2004) and human oocytes (Wu et al 1993). This suggests that a paracrine effect of estrogens is exerted on oocyte maturation.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that a paracrine effect of estrogens is exerted on oocyte maturation. Indeed, Zachos et al (2004) reported that estrogens regulate the formation and maintenance of oocyte microvilli, which are essential for oocyte health and survival. Moreover, the use of aromatase inhibitors significantly reduced the number of microvilli and caused other morphological changes including cytoplasmic vacuolization.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, persistent follicular cysts have been noted in sheep exposed prenatally to T, but not to DHT [33,166], while IUGR and LH surge defects occur in similarly treated sheep exposed to bisphenol, an estrogenic endocrinedisrupting compound [167]. At the ovarian level, reduced primordial follicle numbers occur in ovaries of late gestational fetal baboons following maternal exposure to an aromatase inhibitor [168], while decreased oocyte-granulosa cell microvilli, and presumably perturbed oocyte-granulosa cell signaling, characterize the maturing fetal ovary following diminished estrogen exposure [169,170].…”
Section: Alternate Mechanisms Of Developmental Programmingmentioning
confidence: 99%
“…Using our nonhuman primate baboon model for studies of human reproduction [2,3], we showed that placental estrogen, the levels of which increase with advancing gestation in humans and nonhuman primates [4], regulates fetal ovarian follicle development [5,6]. Thus, in baboons in which estrogen was suppressed by treatment with the aromatase inhibitor letrozole during the second half of gestation, the number of primordial follicles formed in the fetal ovary was reduced by more than 50% [6], and the majority of follicles that developed contained unhealthy oocytes [7]. Additional studies showed that this critical action of estrogen most likely is elicited directly on the fetal ovary, which expresses estrogen receptor (ER) a/b [8,9], and not indirectly via fetal pituitary gonadotrophin support, fetal ovarian follicle-stimulating hormone (FSH) receptor expression [10], or fetal pituitary prolactin secretion [11].…”
Section: Introductionmentioning
confidence: 99%